Synthesis, characterization and excellent catalytic activity of modified ZnO photocatalyst for RR 120 dye degradation under UV-A and solar light illumination. (October 2016) - Kumar, A.; Subash, B.; Krishnakumar, Balu; Sobral, Abilio J.F.N.; Sankaran, K.R.
Graphical abstract: Highlights: SnO2 -Ag-ZnO was successfully synthesized by precipitation-decomposition method. The catalyst is found to be stable and reusable. Treatment of dye effluent using SnO2 -Ag-ZnO will be more economical and eco-friendly. A dual mechanism has been proposed for efficient removal of dye under solar light. Abstract: The different wt% of SnO2 loaded Ag-ZnO (SnO2 –Ag-ZnO) was successfully synthesized by precipitation-decomposition method. The prepared composites were tested towards RR 120 dye degradation under UV-A and direct solar light. 4 wt% SnO2 -Ag-ZnO was found to be more efficient than Ag-ZnO, SnO2 -ZnO, Ag-SnO2, commercial ZnO, bare ZnO, TiO2 -P25 and TiO2 (Merck) at pH 7 for the mineralization of RR 120 under UV and solar light. Hence, this catalyst was characterized by different characterization techniques. The effects of operational parameters such as the amount of photocatalyst, dye concentration, initial pH on photo mineralization of RR 120 have been analyzed. The mineralization of RR 120 has been confirmed by COD measurements. This catalyst is found to be stable and reusable.